Digital Responsibility – a Multilevel Framework for Responsible Digitalization - Beverungen, Daniel; Kundisch, Dennis; Mirbabaie, Milad; Müller, Oliver; Schryen, Guido; Trang, Simon Thanh-Nam; Trier, Matthias (Business & Information Systems Engineering)

Hybrid Intelligence in Hospitals: Towards a Research Agenda for Collaboration and Team-Building - Mirbabaie, Milad; Stieglitz, S.; Frick, N. (Electronic Markets)

The Development of Connective Action during Social Movements on Social Media - Mirbabaie, Milad; Brünker, F.; Wischnewski, M.; Meinert, J. (ACM Transactions on Social Computing)

Affording Technology in Crisis Situations: The Occurrence of Rumor Sense-Making Processes - Mirbabaie, Milad; Stieglitz, Stefan; Amojo, Ireti (Journal of Database Management)

Understanding Collaboration with Virtual Assistants – The Role of Social Identity and Extended Self - Mirbabaie, Milad; Stieglitz, S.; Brünker, F.; Hofeditz, L.; Ross, B.; Frick, N.R.J. (Business & Information Systems Engineering)

Digital Nudging in Social Media Disaster Communication - Mirbabaie, Milad; Ehnis, C.; Stieglitz, S.; Bunker, D.; Rose, T. (Information Systems Frontiers)

Dynamics of Convergence Behaviour in Social Media Crisis Communication – A Complexity Perspective on Peoples’ Behaviour - Mirbabaie, Milad; Stieglitz, S.; Brünker, F. (Information Technology & People)

Ethical Management of Artificial Intelligence - Brendel, A.B.; Mirbabaie, Milad; Lembcke, T.B.; Hofeditz, L. (Sustainability)

Driving Digital Transformation During a Pandemic: Study of Virtual Collaboration in a German Hospital - Mirbabaie, Milad; Stieglitz, S.; Frick, N.R.J.; Möllmann, H.L. (Journal of Medical Internet Research Medical Informatics)

Digital Facilitation Assistance for Collaborative, Creative Design Processes - Bittner, E.; Mirbabaie, Milad; Morana, S. (54th Hawaii International Conference System Sciences)

Is Making Mistakes Human? On the Perception of Typing Errors in Chatbot Communication - Bührke, J.; Brendel, A.B.; Lichtenberg, S.; Greve, M.; Mirbabaie, Milad (54th Hawaii International Conference System Sciences)

Maneuvering through the stormy seas of digital transformation: the impact of empowering leadership on the AI readiness of enterprises - Frick, Nicholas R. J.; Mirbabaie, Milad; Stieglitz, Stefan; Salomon, Jana (Journal of Decision Systems)

Understanding Collaboration with Virtual Assistants – The Role of Social Identity and the Extended Self - Mirbabaie, Milad; Stieglitz, Stefan; Brünker, Felix; Hofeditz, Lennart; Ross, Björn; Frick, Nicholas R. J. (Business & Information Systems Engineering)
Abstract Organizations introduce virtual assistants (VAs) to support employees with work-related tasks. VAs can increase the success of teamwork and thus become an integral part of the daily work life. However, the effect of VAs on virtual teams remains unclear. While social identity theory describes the identification of employees with team members and the continued existence of a group identity, the concept of the extended self refers to the incorporation of possessions into one’s sense of self. This raises the question of which approach applies to VAs as teammates. The article extends the IS literature by examining the impact of VAs on individuals and teams and updates the knowledge on social identity and the extended self by deploying VAs in a collaborative setting. Using a laboratory experiment with N = 50, two groups were compared in solving a task, where one group was assisted by a VA, while the other was supported by a person. Results highlight that employees who identify VAs as part of their extended self are more likely to identify with team members and vice versa. The two aspects are thus combined into the proposed construct of virtually extended identification explaining the relationships of collaboration with VAs. This study contributes to the understanding on the influence of the extended self and social identity on collaboration with VAs. Practitioners are able to assess how VAs improve collaboration and teamwork in mixed teams in organizations.

Dynamics of convergence behaviour in social media crisis communication – a complexity perspective - Mirbabaie, Milad; Stieglitz, Stefan; Brünker, Felix (Information Technology & People)

Artificial intelligence in disease diagnostics: A critical review and classification on the current state of research guiding future direction - Mirbabaie, Milad; Stieglitz, Stefan; Frick, Nicholas R. J. (Health and Technology)
The diagnosis of diseases is decisive for planning proper treatment and ensuring the well-being of patients. Human error hinders accurate diagnostics, as interpreting medical information is a complex and cognitively challenging task. The application of artificial intelligence (AI) can improve the level of diagnostic accuracy and efficiency. While the current literature has examined various approaches to diagnosing various diseases, an overview of fields in which AI has been applied, including their performance aiming to identify emergent digitalized healthcare services, has not yet been adequately realized in extant research. By conducting a critical review, we portray the AI landscape in diagnostics and provide a snapshot to guide future research. This paper extends academia by proposing a research agenda. Practitioners understand the extent to which AI improves diagnostics and how healthcare benefits from it. However, several issues need to be addressed before successful application of AI in disease diagnostics can be achieved.

Artificial intelligence in hospitals: providing a status quo of ethical considerations in academia to guide future research - Mirbabaie, Milad; Hofeditz, Lennart; Frick, Nicholas R. J.; Stieglitz, Stefan (AI & SOCIETY)
Abstract The application of artificial intelligence (AI) in hospitals yields many advantages but also confronts healthcare with ethical questions and challenges. While various disciplines have conducted specific research on the ethical considerations of AI in hospitals, the literature still requires a holistic overview. By conducting a systematic discourse approach highlighted by expert interviews with healthcare specialists, we identified the status quo of interdisciplinary research in academia on ethical considerations and dimensions of AI in hospitals. We found 15 fundamental manuscripts by constructing a citation network for the ethical discourse, and we extracted actionable principles and their relationships. We provide an agenda to guide academia, framed under the principles of biomedical ethics. We provide an understanding of the current ethical discourse of AI in clinical environments, identify where further research is pressingly needed, and discuss additional research questions that should be addressed. We also guide practitioners to acknowledge AI-related benefits in hospitals and to understand the related ethical concerns.

CYWARN: Strategy and Technology Development for Cross-Platform Cyber Situational Awareness and Actor-Specific Cyber Threat Communication - Kaufhold, M.-A.; Riebe, T.; Kühn, P.; Bayer, M.; Reuter, C.; Stöttinger, M.; Möller, R.; Mirbabaie, Milad; Fromm, J.; Basyurt, A.S.; Stieglitz, S.; Eyilmez, K.; et al. (Proceedings of the 8th Mensch und Computer)

Teaching the Smart Home - User Experience in an Interactive Learning Phase - Sieger, L. N.; Doğangün, A.; Mirbabaie, Milad (Proceedings of the 8th Mensch und Computer)

Social Media Analytics and Corporate Crises - A Case Study of Boeing's 737 Max Crashes - Marx, J.; Mirbabaie, Milad; Czonstke, C.; Stieglitz, S. (29th European Conference on Information Systems)

Do you trust an AI-Journalist? A Credibility Analysis of News Content with AI-Authorship - Hofeditz, L.; Mirbabaie, Milad; Holstein, J.; Stieglitz, S. (29th European Conference on Information Systems)

The Role of Parasocial Interactions for Podcast Backchannel Response - Marx, J.; Mirbabaie, Milad; Brendel, A.B.; Zander, K. (The Americas Conference on Information Systems)

Ausgestaltungs- und Anwendungspotenziale von Virtual und Augmented Reality Technologien im Kontext von Coworking Spaces - Mirbabaie, Milad; Hofeditz, Lennart; Schmid, Leon (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Coworking Spaces (CSPs) sind geteilte Arbeitsplätze für Selbstständige, Freelancer*innen, Mikrounternehmen und Startups, die Isolation entgegenwirken und zum interdisziplinären Wissensaustausch anregen können. Jedoch existieren auch Barrieren, die Nutzer*innen davon abhalten, zu anderen Coworker*innen Kontakt aufzunehmen, da oft unklar ist, wann und ob jemand zum kreativen Austausch oder zum Anbieten von Hilfe bereit ist. Durch die Covid-19 Pandemie wurde die Unsicherheit bei der gegenseitigen Kontaktaufnahme noch weiter erschwert und viele CSPs mussten zeitweise schließen. Um Barrieren bei der Kontaktaufnahme zu reduzieren und die interdisziplinäre Zusammenarbeit zu fördern, können Informations- und Kommunikationstechnologien eingesetzt werden. Virtual Reality (VR) und Augmented Reality (AR) sind Technologien, die sich durch einen besonders hohen Grad an Immersion und sozialer Präsenz auszeichnen. Deshalb zeigen wir in diesem Beitrag, wie VR- und AR-Technologien gezielt eingesetzt werden können, um den interdisziplinären Wissensaustausch und Zusammenarbeit sowohl in CSPs als auch ortsunabhängig zu fördern. Dazu präsentieren wir positive Effekte, die durch den Einsatz einer der beiden Technologien im Zusammenhang mit CSPs erzielt werden können und leiten konkrete Gestaltungsempfehlungen für Anwendungsentwickler*innen, Unternehmen sowie Betreiber*innen von CSPs ab. Diese Gestaltungsempfehlungen basieren sowohl auf den neuesten Erkenntnissen aus der Fachliteratur als auch auf Interviews mit Expert*innen aus Forschung und Praxis mit Erfahrung im Bereich CSPs, VR und AR. Unsere Anwendungsszenarien können Entwickler*innen, Unternehmen und Betreiber*innen von CSPs als Grundlage dienen, vom Einsatz beider Technologien zu profitieren.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Affordance-Experimentation: Eine Fallstudie zur Entwicklung von Virtual-Reality-Anwendungsfällen im Unternehmenskontext - Fromm, Jennifer; Slawinski, Elena; Mirbabaie, Milad (HMD Praxis der Wirtschaftsinformatik)
Zusammenfassung Durch technologische Fortschritte in den letzten Jahren ist Virtual Reality erschwinglicher und benutzerfreundlicher geworden, sodass Unternehmen die Einführung der Technologie verstärkt in Betracht ziehen. Ihren Aufschwung erlebte die Technologie jedoch durch die Unterhaltungs- und Spieleindustrie, weshalb sich für Unternehmen die Frage nach sinnvollen Anwendungsfällen stellt. Nach der Affordance-Experimentation-Actualization-Theorie ist insbesondere bei neu aufkommenden Technologien eine Experimentierphase notwendig, um Handlungsmöglichkeiten aufzudecken und daraus Anwendungsfälle zu generieren. Dieser Artikel präsentiert die Ergebnisse einer Fallstudie in einem Unternehmen, das sich während der Studie in der Experimentierphase befand. Durch Interviews mit acht Beschäftigten und einem Vertriebspartner konnten drei Handlungsmöglichkeiten für Virtual Reality im Unternehmenskontext und eine zuvor nicht bekannte Aktivität der Experimentierphase identifiziert werden. Damit erweitert die Studie bisherige Forschung zur Experimentierphase und zeigt Unterschiede im Vergleich zu anderen innovativen Technologien auf, die in vorherigen Studien untersucht wurden. Für Unternehmen bietet die Studie wertvolle Einblicke in die erfolgreiche Gestaltung der Experimentierphase als Vorbereitung auf die Implementierung.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Social media in times of crisis: Learning from Hurricane Harvey for the coronavirus disease 2019 pandemic response - Mirbabaie, Milad; Bunker, Deborah; Stieglitz, Stefan; Marx, Julian; Ehnis, Christian (Journal of Information Technology)
In recent times societal crises such as the coronavirus disease 2019 outbreak have given rise to a tension between formal ‘command and control’ and informal social media activated self-organising information and communication systems that are utilised for crisis management decision-making. Social media distrust affects the dissemination of disaster information as it entails shifts in media perception and participation but also changes in the way individuals and organisations make sense of information in critical situations. So far, a little considered notion in this domain is the concept of sense-giving. Originating from organisational theory, it is used to explain the mechanisms behind intentional information provision that fosters collective meaning creation. In our study, we seek to understand the potential impact of sense-giving from Twitter crisis communication generated during the Hurricane Harvey disaster event. Social network and content analyses performed with a dataset of 9,414,463 tweets yielded insights into how sense-giving occurs during a large-scale disaster event. Theoretically, we specified (1) perpetual sense-giving, which relies primarily on topical authority and frequency; as well as (2) intermittent sense-giving, which occurs from high value of message content and leverage of popularity, that is, retweets. Our findings emphasise the importance of information-rich actors in communication networks and the leverage of their influence in crises such as coronavirus disease 2019 to reduce social media distrust and facilitate sense-making.

When are researchers willing to share their data? – Impacts of values and uncertainty on open data in higher education - Stieglitz, Stefan; Wilms, Konstantin; Mirbabaie, Milad; Hofeditz, Lennart; Brenger, Bela; López, Ania; Rehwald, Stephanie (PLOS ONE)

Virtually Extended Coworking Spaces – The Reinforcement of Social Proximity, Motivation and Knowledge Sharing Through ICT - Hofeditz, L.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 31st Australasian Conference on Information Systems)

Digital Detox – Mitigating Digital Overuse in Times of Remote Work and Social Isolation - Mirbabaie, Milad; Marx, J.; Braun, L.-M.; Stieglitz, S. (Proceedings of the 31st Australasian Conference on Information Systems)

‘Conspiracy Machines’ - The Role of Social Bots during the COVID-19 ‘Infodemic’ - Marx, J.; Brünker, F.; Mirbabaie, Milad; Hochstrate, E. (Proceedings of the 31st Australasian Conference on Information Systems)

A Systematic Review of Empirical Affordance Studies: Recommendations for Affordance Research in Information Systems - Fromm, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the Twenty-Eight European Conference on Information Systems)

The Usage of Twitter Data for Early Crisis Detection - Mirbabaie, Milad; Stieglitz, S.; Lambertz, L. (Proceedings of the 15th International Conference on Wirtschaftsinformatik)

‘The Tireless Selling-Machine’ – Commercial Deployment of Social Bots during Black Friday Season on Twitter - Brünker, F.; Marx, J.; Ross, B.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 15. Internationaler Kongress Für Wirtschaftsinformatik)

The Effects of Virtual Reality Affordances and Constraints on Negative Group Effects during Brainstorming Sessions - Fromm, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 15. Internationaler Kongress Für Wirtschaftsinformatik)

The Role of Social Media during Social Movements – Observations from the #metoo Debate on Twitter - Brünker, F.; Wischnewski, M.; Mirbabaie, Milad; Meinert, J. (Proceedings of the 51nd Hawaii International Conference on System Sciences)

Who Sets the Tone? Determining the Impact of Convergence Behaviour Archetypes in Social Media Crisis Communication - Mirbabaie, Milad; Bunker, D.; Stieglitz, S. (Information Systems Frontiers)

‘Silence’ as a Strategy during a Corporate Crisis - The Case of Volkswagen’s ‘Dieselgate’ - Stieglitz, S.; Mirbabaie, Milad; Kroll, T.; Marx, J. (Internet Research)

‘Breaking’ News: Uncovering Sense-Breaking Patterns in Social Media Crisis Communication during the 2017 Manchester Bombing - Mirbabaie, Milad; Marx, J. (Behaviour & Information Technology)

Challenges and Opportunities of Artificial Intelligence for Incident Management - Mirbabaie, Milad; Hellmann, M. (Proceedings of the IFIP 8.2 OASIS Workshop on Post-Digitalization 2019)

Collective Identity Formation on Instagram – Investigating the Social Movement Fridays for Future - Brünker, F.; Deitelhoff, F.; Mirbabaie, Milad (Proceedings of the 30th Australasian Conference on Information Systems)

Reducing the Cognitive Load of Decision-Makers in Emergency Management through Augmented Reality - Mirbabaie, Milad; Fromm, J. (Proceedings of the Twenty-Seventh European Conference on Information Systems)

Nudging People to save Energy in Smart Homes with Social Norms and Self-Commitment - Kroll, T.; Paukstadt, U.; Kreidermann, K.; Mirbabaie, Milad (Proceedings of the Twenty-Seventh European Conference on Information Systems)

'Show Me Your People Skills' - Employing CEO Branding for Corporate Reputation Management in Social Media - Mirbabaie, Milad; Marx, J.; Stieglitz, S. (Proceedings of the 14th International Conference on Wirtschaftsinformatik)

The Potential of Augmented Reality for Improving Occupational First Aid - Fromm, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 14th International Conference on Wirtschaftsinformatik)

Einsatz von Spielmechaniken und Bots zur Moderation von Kreativitätsprozessen in Unternehmen - Mirbabaie, Milad; Stieglitz, Stefan; Priesmeyer, Jessica; Kindel, Marius (HMD Praxis der Wirtschaftsinformatik)

Social Media Analytics - Challenges in Topic Discovery, Data Collection, and Data Preparation - Stieglitz, S.; Mirbabaie, Milad; Ross, B.; Neuberger, C. (International Journal of Information Management)

Going Back in Time to Predict the Future - The Complex Role of the Data Collection Period in Social Media Analytics - Stieglitz, S.; Meske, C.; Ross, B.; Mirbabaie, Milad (Information Systems Frontiers)

Understanding Sense-Making on Social Media during Crises: Categorization of Sense-Making Barriers and Strategies - Stieglitz, S.; Mirbabaie, Milad; Fromm, J. (International Journal of Information Systems for Crisis Response and Management)

Interaction and Influence on Twitter: Comparing the discourse relationships between user types on five topics - Kapidzic, Sanja; Neuberger, Christoph; Stieglitz, Stefan; Mirbabaie, Milad (Digital Journalism)

Social Positions and Collective Sense-making in Crisis Communication - Stieglitz, S.; Mirbabaie, Milad; Milde, M. (International Journal of Human-Computer Interaction)

Information Diffusion between Twitter and Online Media - Jung, A.-K.; Mirbabaie, Milad; Ross, B.; Stieglitz, S.; Neuberger, C.; Kapidzic, S. (Proceedings of the 39th International Conference on Information Systems)

The Potential of Social Media Analytics for Improving Social Media Communication of Emergency Agencies - Mirbabaie, Milad; Fromm, J.; Löppenberg, S.; Meinig, S.; Reuße, M. (Proceedings of the 29th Australasian Conference on Information Systems)

Sense-Giving Strategies of Media Organisations in Social Media Disaster Communication: Findings from Hurricane Harvey - Marx, J.; Mirbabaie, Milad; Ehnis, C. (Proceedings of the 29th Australasian Conference on Information Systems)

You are now an Influencer! Measuring CEO Reputation in Social Media - Marx, J.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 29th Australasian Conference on Information Systems)

Threat or Opportunity? - Examining Social Bots in Social Media Crisis Communication - Brachten, F.; Mirbabaie, Milad; Stieglitz, S.; Berger, O.; Bludau, S.; Schrickel, K. (Proceedings of the 29th Australasian Conference on Information Systems)

The Adoption of Social Media Analytics for Crisis Management – Challenges and Opportunities - Stieglitz, S.; Mirbabaie, Milad; Fromm, J.; Melzer, S. (Proceedings of the Twenty-Sixth European Conference on Information Systems)

"Is it really fake? – Towards an Understanding of Fake News in Social Media Communication" - Meinert, J.; Mirbabaie, Milad; Dungs, S.; Aker, A. (20th International Conference on Human-Computer Interaction, Social Computing and Social Media)

The Quality of Tweets and the Adoption of Journalistic Norms - Kapidzic, Sanja; Neuberger, Christoph; Stieglitz, Stefan; Mirbabaie, Milad (Trust in Media and Journalism: Empirical perspectives on ethics, norms, impacts and populism in Europe)

Exploring Sense-making Activities in Crisis Situations - Mirbabaie, Milad; Youn, S. (Proceedings of the 10th Multikonferenz Wirtschaftsinformatik)

Integration von Social-Media-Daten in analytische CRM-Systeme - Mirbabaie, Milad; Potthoff, T.; Lange, C.; Stieglitz, S. (Proceedings of the 10th Multikonferenz Wirtschaftsinformatik)

Crisis Communication on Twitter during a Global Crisis of Volkswagen – The Case of “Dieselgate” - Stieglitz, S.; Mirbabaie, Milad; Potthoff, T. (Proceedings of the 51st Hawaii International Conference on System Sciences)

Sense-Making in Social Media During Extreme Events - Stieglitz, Stefan; Bunker, Deborah; Mirbabaie, Milad; Ehnis, Christian (Journal of Contingencies and Crisis Management)

Convergence Behaviour of Bystanders: An Analysis of 2016 Munich Shooting Twitter Crisis Communication - Bunker, D.; Mirbabaie, Milad; Stieglitz, S. (Proceedings of the 28th Australasian Conference on Information Systems)

Sensemaking in Social Media Crisis Communication - A Case Study on the Brussels Bombings in 2016 - Mirbabaie, Milad; Zapatka, E. (Proceedings of the Twenty-Fifth European Conference on Information Systems)

#IronyOff – Understanding the Usage of Irony on Twitter during a Corporate Crisis - Mirbabaie, Milad; Stieglitz, S.; Ruiz Eiro, M. (Proceedings of the 21st Pacific Asia Conference on Information Systems)

Mobile Unterstützung für Hilfsorganisationen in Krisensituationen - Anforderungsanalyse und prototypische Umsetzung einer Smartwatch App - Mirbabaie, Milad; Stieglitz, Stefan; Kubat, Patrick (INFORMATIK 2017)

Sensemaking and Communication Roles in Social Media Crisis Communication - Stieglitz, Stefan; Mirbabaie, Milad; Schwenner, L.; Marx, J.; Lehr, J.; Brünker, F. (Proceedings of the 13th International Conference on Wirtschaftsinformatik)

Geodaten in Social Media als Informationsquelle in Krisensituationen - Mirbabaie, Milad; Tschampel, N.; Stieglitz, Stefan (Proceedings of the 9th Multikonferenz Wirtschaftsinformatik)

Volunteered Geographic Information and its Implications for Disaster Management - Mirbabaie, Milad; Stieglitz, Stefan; Volkeri, S. (Proceedings of the 49th Hawaii International Conference on System Sciences)

Communication roles in public events: a case study on Twitter communications - Mirbabaie, Milad; Ehnis, Christian; Stieglitz, Stefan; Bunker, Deborah (Information systems and global assemblages: (re)configuring actors, artefacts, organizations: IFIP WG 8.2 Working Conference on Information Systems)

How context impacts on media choice - Stieglitz, Stefan; Brockmann, Tobias; Mirbabaie, Milad (Proceedings of the 25th Australasian Conference on Information Systems)

The role of social media network participants in extreme events - Ehnis, Christian; Mirbabaie, Milad; Bunker, Deborah; Stieglitz, Stefan (Proceedings of the 25th Australasian Conference on Information Systems)